2022
DOI: 10.2169/internalmedicine.8581-21
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic Meningitis after Amenamevir Treatment for Herpes Zoster in the First Branch of the Trigeminal Nerve

Abstract: Amenamevir has been approved for the treatment of herpes zoster (HZ); however, its therapeutic efficacy against central nervous system (CNS) infection may be insufficient due to its low spinal fluid permeability. We herein report a case of aseptic meningitis in a 91-year-old Japanese man treated with amenamevir for HZ in the trigeminal nerve region. Several cases of CNS infection have been reported in patients receiving amenamevir treatment for HZ. Patients with CNS complications often have skin rashes near th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…We experienced three cases of aseptic meningitis by VZV and one case of VZV myelitis after HZ dermatitis during treatment with amenamevir for HZ in various immunological backgrounds (Table 1). Table 2 summarizes six HZ cases treated with amenamevir with CNS complications that were previously reported [2][3][4][5][6]. While three cases in our report are regarded as immunocompromised hosts (two cases were taking immunosuppressive drugs, and one case had sigmoid colon cancer as an underlying disease), one case was immunocompetent.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We experienced three cases of aseptic meningitis by VZV and one case of VZV myelitis after HZ dermatitis during treatment with amenamevir for HZ in various immunological backgrounds (Table 1). Table 2 summarizes six HZ cases treated with amenamevir with CNS complications that were previously reported [2][3][4][5][6]. While three cases in our report are regarded as immunocompromised hosts (two cases were taking immunosuppressive drugs, and one case had sigmoid colon cancer as an underlying disease), one case was immunocompetent.…”
Section: Discussionmentioning
confidence: 76%
“…In the outpatient setting, amenamevir may be a more frequent prescription choice, especially for elderly patients with HZ, as no volume adjustment based on creatinine clearance is necessary. However, for immunocompromised patients, such as those taking immunosuppressive medications, or for ocular HZ patients at a high risk of CNS complications, as in the present cases, it may be preferable to use acyclovir or valacyclovir to reduce the risk of complications [ 5 ]. Additionally, Skripuletz et al conducted a study on VZV CNS complications and found that cardiovascular diseases were the most common comorbidity, followed by impaired renal function [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms result from the inflammatory processes and the resulting irritation of the meninges and surrounding nervous tissue. 147 The diagnosis of VZV-associated aseptic meningitis often involves the detection of VZV-specific antibodies or viral DNA in the CSF. Antiviral therapy, along with supportive care and management of symptoms, is essential in reducing viral replication, controlling the inflammatory response, and improving clinical outcomes in affected individuals.…”
Section: Aseptic Meningitismentioning
confidence: 99%
“…Aseptic meningitis associated with VZV infection typically presents with symptoms such as headache, fever, neck stiffness, photophobia, and neurological deficits. These symptoms result from the inflammatory processes and the resulting irritation of the meninges and surrounding nervous tissue 147 . The diagnosis of VZV‐associated aseptic meningitis often involves the detection of VZV‐specific antibodies or viral DNA in the CSF.…”
Section: Role Of Vzv Infection In Inflammatory Neurological Diseasesmentioning
confidence: 99%